The association between abnormal vaginal microbial flora and preterm labor. Does a simple Gram’s stain of vaginal swab gives more useful data than culture ? - Al Shamma’a, Haider (Journal of the Faculty of Medicine Baghdad, 2014)
Fac Med Baghdad 2014; Vol.56, No.2 Received: Jan., 2014 Accepted March. 2014 Background: Preterm labor is the major cause of perinatal mortality and morbidity and it is a challenging obstetrical complication as treatment is marginally effective if ever and no improvement in incidence over the last 5 decades , although may causes were identified the majority are idiopathic and in this category infection seems to be involved as a causative agent Objectives: to evaluate the association of abnormal vaginal flora diagnosed by direct Gram’s staining and vaginal culture with preterm labor. Patients, material and methods: 25 women with preterm labor compared with 25 women at full term pregnancy, high vaginal swabs for direct Gram’s staining (Spiegel criteria for abnormal vaginal flora) and culture. The results were compared in both group Results: this study showed significant association between preterm labor and abnormal vaginal flora 7 (28%) and 12 (48%) of grade II and III respectively . and a significant association between term pregnancy and normal vaginal flora 16 (64%) of grade I. Also in the presence of abnormal vaginal flora, no significant association with type of pathogenic microorganism and preterm labor as all types may be associated with PTL , and the presence of Lactobacillus spp. (normal grade I flora ) is associated with term pregnancy. Conclusions: Gram’s staining of high vaginal swab using Spiegel criteria can be useful simple test to predict preterm labor